Localisation of PGK1 determines metabolic phenotype to balance metastasis and proliferation in patients with SMAD4-negative pancreatic cancer. Issue 5 (14th October 2019) - Liang, Chen; Shi, Si; Qin, Yi; Meng, Qingcai; Hua, Jie; Hu, Qiangshen; Ji, Shunrong; Zhang, Bo; Xu, Jin; Yu, Xian-Jun
Abstract : Objective: Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive type of GI tumour, and it possesses deregulated cellular energetics. Although recent advances in PDAC biology have led to the discovery of recurrent genetic mutations in Kras, TP53 and SMAD4, which are related to this disease, clinical application of the molecular phenotype of PDAC remains challenging. Design: We combined molecular imaging technology (positron emission tomography/CT) and immunohistochemistry to evaluate the correlation between the maximum standardised uptake value and SMAD4 expression and examined the effect of SMAD4 on glycolysis through in vitro and in vivo experiments. Furthermore, we identified the effect of SMAD4 on metabolic reprogramming by metabolomics and glucose metabolism gene expression analyses. Dual luciferase reporter assays and chromatin immunoprecipitation were performed to identify whether SMAD4 functioned as a transcription factor for phosphoglycerate kinase 1 (PGK1) in PDAC cells. Proliferative and metastatic assays were performed to examine the effect of PGK1 on the malignant behaviour of PDAC. Results: We provide compelling evidence that the glycolytic enzyme PGK1 is repressed by transforming growth factor-β/SMAD4. Loss of SMAD4 induces PGK1 upregulation in PDAC, which enhances glycolysis and aggressive tumour behaviour. Notably, in SMAD4-negative PDAC, nuclear PGK1 preferentially drives cell metastasis via mitochondrial oxidative phosphorylation induction, whereas cytoplasmic PGK1 preferentially supports proliferation by functioning as a glycolytic enzyme. The PDAC progression pattern and distinct PGK1 localisation combine to predict overall survival and disease-free survival. Conclusion: PGK1 is a decisive oncogene in patients with SMAD4-negative PDAC and can be a target for the development of a therapeutic strategy for SMAD4-negative PDAC.